Biophysical and socioeconomic factors influencing soil carbon stocks: a global assessment. Appendix S1: Raw Dataset [Conjunto de datos] - Duarte Guardia, Sandra; Peri, Pablo Luis; Amelung, Wulf; Thomas, Evert; Borchard, Nils; Baldi, Germán; Cowie, Annette L.; Ladd, Brenton (Grupo de Investigación Forestal-Silvopastoril. Instituto Nacional de Tecnología Agropecuaria (INTA), EEA Santa Cruz; Universidad Nacional de la Patagonia Austral (UNPA); Centro Austral de Investigaciones Científicas (CADIC-CONICET)., 2020)
Supplementary information of the: Duarte-Guardia, S., Peri, P., Amelung, W. et al. Biophysical and socioeconomic factors influencing soil carbon stocks: a global assessment. Mitig Adapt Strateg Glob Change 25, 1129–1148 (2020). EEA Santa Cruz Fil: Duarte Guardia, Sandra. Universidad Nacional de la Patagonia Austral; Argentina. Fil: Peri, Pablo Luis. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral (UNPA). Santa Cruz; Argentina. Fil: Peri, Pablo Luis. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET); Argentina. Fil: Amelung, Wulf. University of Bonn. Soil Science and Soil Ecology. Institute of Crop Science and Resource Conservation (INRES). Bonn; Alemania. Fil: Thomas, Evert. Bioversity International. Lima; Perú. Fil: Borchard, Nils. Natural Resources Institute Finland (Luke). Plant Production. Helsinki; Finlandia. Fil: Baldi, Germán. Universidad Nacional de San Luis. Instituto de Matemática Aplicada. San Luis; Argentina. Fil: Baldi, Germán. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET). San Luis; Argentina. Fil: Cowie, Annette L. NSW Department of Primary Industries. Armidale. NSW; Australia. Fil: Cowie, Annette L. University of New England. School of Environmental and Rural Science. Armidale. NSW; Australia. Fil: Ladd, Brenton. Universidad Científica del Sur. Escuela de Agroforestería. Lima; Perú.